2014
DOI: 10.1590/s1984-29612014078
|View full text |Cite
|
Sign up to set email alerts
|

Serological detection of Toxoplasma gondii, Leishmania infantum and Neospora caninum in cats from an area endemic for leishmaniasis in Brazil

Abstract: An investigation was made into the occurrence of antibodies to Toxoplasma gondii, Leishmania infantum and Neospora caninum in 151 domestic cats, based on the indirect fluorescent antibody test (IFAT). Serum samples were collected from 151 domestic cats (65 free-roaming and 86 domiciled cats; 55 males and 96 females) in Campo Grande, Mato Grosso do Sul, Brazil between January and April 2013. IgG antibodies to T. gondii, L. infantum and N. caninum were found, respectively, in 49 (32.5%), 34 (22.5%) and 10 (6.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
3
16
1
4
Order By: Relevance
“…The FeL seropositivity here was higher than that observed in Recife and Teresina, where 3.9% and 4% of the cats were found be seropositive for FeL using ELISA (SILVA et al, 2014;MENDONÇA et al, 2017). Sero-epidemiological investigations in other regions of the country found frequencies varying from 0.5% to 54%, using IFAT and the same cut-off value adopted here (1:40) (VIDES et al, 2011;CARDIA et al, 2013;BRAGA et al, 2014;SOUSA et al, 2014;OLIVEIRA et al, 2015;GODOI et al, 2016;COURA et al, 2018;MATOS et al, 2018). In canine leishmaniasis, high serological titers (four times the established cut-off value) with clinical signs compatible with leishmaniasis are diagnostic for the disease (SOLANO-GALLEGO et al, 2011).…”
Section: Introductionmentioning
confidence: 39%
See 1 more Smart Citation
“…The FeL seropositivity here was higher than that observed in Recife and Teresina, where 3.9% and 4% of the cats were found be seropositive for FeL using ELISA (SILVA et al, 2014;MENDONÇA et al, 2017). Sero-epidemiological investigations in other regions of the country found frequencies varying from 0.5% to 54%, using IFAT and the same cut-off value adopted here (1:40) (VIDES et al, 2011;CARDIA et al, 2013;BRAGA et al, 2014;SOUSA et al, 2014;OLIVEIRA et al, 2015;GODOI et al, 2016;COURA et al, 2018;MATOS et al, 2018). In canine leishmaniasis, high serological titers (four times the established cut-off value) with clinical signs compatible with leishmaniasis are diagnostic for the disease (SOLANO-GALLEGO et al, 2011).…”
Section: Introductionmentioning
confidence: 39%
“…In Brazil, studies on FeL using serological, parasitological, and molecular methods revealed that infection frequencies varied from 0% to 54% (BRESCIANI et al, 2010;VIDES et al, 2011;CARDIA et al, 2013;BRAGA et al, 2014;SILVA et al, 2014;SOUSA et al, 2014;OLIVEIRA et al, 2015;GODOI et al, 2016;MENDONÇA et al, 2017;COURA et al, 2018;MATOS et al, 2018). Only a small fraction of these studies was performed in the Northeast region that was home to 82.5% of all reported cases of human leishmaniasis in Brazil between 1980 and 2005, making this region an area of epidemiological relevance for this disease in Brazil (MAIA-ELKHOURY et al, 2008;SILVA et al, 2014;MENDONÇA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ten microliters of two fold dilutions of sera (cut-off of 1:40) were placed in wells on antigen slides. Known positive serum samples for the studied agents were obtained from naturally infected deer [26] and dogs [27] from Brazil. Negative serum samples were obtained from wild deer captured in Brazil [26], and dogs maintained in the kennel of the Department of Veterinary Pathology, UNESP, Jaboticabal, São Paulo, Brazil, that had not been exposed to these agents, according to negative PCR and IFAT results.…”
Section: Serology For Babesia Vogeli Anaplasma Phagocytophilum Ehrlmentioning
confidence: 99%
“…In dogs, T. gondii generally does not cause primary infection unless preceded by an immunosuppressive disease [33]. A significant association has previously been found in several studies between L. infantum and T. gondii in dogs, suggesting that the immunosuppression caused by L. infantum may enhance the susceptibility of dogs to T. gondii [31,32,34]. However, this hypothesis lacks scientific corroboration.…”
Section: Similar Findings Have Been Reported By Other Researchersmentioning
confidence: 99%